IL‐18 neutralization during alveolar hypoxia improves left ventricular diastolic function in mice. (24th September 2014) - Hillestad, V.; Espe, E. K. S.; Cero, F.; Larsen, K. O.; Sjaastad, I.; Nygård, S.; Skjønsberg, O. H.; Christensen, G.
Abstract Aim In patients, an association exists between pulmonary diseases and diastolic dysfunction of the left ventricle (LV). We have previously shown that alveolar hypoxia in mice induces LV diastolic dysfunction and that mice exposed to hypoxia have increased levels of circulating interleukin‐18 (IL‐18), suggesting involvement of IL‐18 in development of diastolic dysfunction. IL‐18 binding protein (IL‐18BP) is a natural inhibitor of IL‐18. In this study, we hypothesized that neutralization of IL‐18 during alveolar hypoxia would improve LV diastolic function. Methods Mice were exposed to 10% oxygen for 2 weeks while treated with IL‐18BP or vehicle. Cardiac function and morphology were measured using echocardiography, intraventricular pressure measurements and magnetic resonance imaging (MRI). For characterization of molecular changes in the heart, both real‐time PCR and Western blotting were performed. ELISA technique was used to measure levels of circulating cytokines. Results As expected, exposure to hypoxia‐induced LV diastolic dysfunction, as shown by prolonged time constant of isovolumic relaxation (τ). Improved relaxation with IL‐18BP treatment was demonstrated by a significant reduction towards control τ values. Decreased levels of phosphorylated phospholamban (P‐PLB) in hypoxia, but normalization by IL‐18BP treatment suggest a role for IL‐18 in regulation of calcium‐handling proteins in hypoxia‐induced diastolic dysfunction. In addition, MRI showed less increase in right ventricular (RV) wall thickness in IL‐18BP‐treated animals exposed to hypoxia, indicating an effect on RV hypertrophy. Conclusion Neutralization of IL‐18 during alveolar hypoxia improves LV diastolic function and partly prevents RV hypertrophy.